Bessel wavelet transform on the spaces with exponential growth - Upadhyay S.K.; Singh R. (My University, 2025)
The Bessel wavelet transform on χµ and Qµ type spaces of exponential growth are investigated and their properties discussed by using the theory of the Hankel transform. Using this said theory, the integral equation of Fredholm type is defined and some examples associated with this integral equation are given. © 2017, University of Nis. All rights reserved.